2003
DOI: 10.1128/mcb.23.1.259-271.2003
|View full text |Cite
|
Sign up to set email alerts
|

Novel Transcriptional Potentiation of BETA2/NeuroD on the Secretin Gene Promoter by the DNA-Binding Protein Finb/RREB-1

Abstract: The basic helix-loop-helix protein BETA2/NeuroD activates transcription of the secretin gene and is essential for terminal differentiation of secretin-producing enteroendocrine cells. However, in heterodimeric complexes with its partner basic helix-loop-helix proteins, BETA2 does not appear to be a strong activator of transcription by itself. Mutational analysis of a proximal enhancer in the secretin gene identified several cis-acting elements in addition to the E-box binding site for BETA2. We identified by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 44 publications
1
52
0
Order By: Relevance
“…Gel shift assays and nuclear extract preparation were performed as described earlier (28). For reconstitution of DNA-protein complexes using recombinant Sp1 (Promega) or in vitro-translated proteins, 0.25 g of poly(dI-dC) was used in each assay.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Gel shift assays and nuclear extract preparation were performed as described earlier (28). For reconstitution of DNA-protein complexes using recombinant Sp1 (Promega) or in vitro-translated proteins, 0.25 g of poly(dI-dC) was used in each assay.…”
Section: Methodsmentioning
confidence: 99%
“…Our earlier work suggested that NeuroD1 is a relatively weak yet essential transcriptional activator of the secretin gene (28). The organization of the secretin enhancer bears little similarity to that of the insulin or POMC enhancers, suggesting that the function of NeuroD1 in transcription of the secretin, insulin, and POMC genes in enteroendocrine cells, pancreatic ␤ cells, and pituitary corticotrophs, respectively, may depend on other factors recruited to each enhancer.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…10 The significance of RREB1 continues to be elucidated as studies have found it to function in either the induction or repression of gene expression. Genes induced by RREB1 include those encoding calcitonin, 11 FSH, 12 MT-IIA, 13 p53, 14 and secretin 15 ; genes repressed by RREB1 include those encoding angiotensinogen, 16 HLA-G, 17 hZIP1, 18 p16, 19 and PSA. 20 RREB1 has also been found to bind nuclear proteins, such as CtBP, 21 NeuroD, 15 and androgen receptor (AR).…”
mentioning
confidence: 99%